Perceptions of HIV/AIDS Testing Among Urban and Rural African American Church Members - Roblena Walker (Georgia Southern University, 2015)
Background: The prevalence of the human immunodeficiency virus (HIV) continues to affect African Americans (AA) disproportionately. The purpose of this mixed methods study, guided by the health belief model, was to examine associations linking church and ambient social environment with knowledge and perceptions of HIV/AIDS testing amongst urban and rural AA church members. Methods: Multiple regressions and t tests were used to compare perceptions of HIV/AIDS testing and knowledge of HIV/AIDS among 236 participants selected from two AA churches located in a large city (n = 122) and in a rural town (n =114) in the Southern U.S. Results: The quantitative findings indicated that the urban participants reported significantly higher rates of testing than the rural participants, but the groups had equally high HIV knowledge and positive perceptions of HIV/AIDS testing. In-depth, individual interviews (24 urban; 24 rural) were conducted to gain a better understanding of the factors that contribute to perceptions of HIV/AIDS testing and knowledge of HIV/AIDS. Transcripts were axially coded for a priori themes and then analyzed for emergent categories of responses. These interviews indicated that the participant's perceptions of HIV/AIDS testing were in general, not influenced by the church and that there were no noticeable distinctions regarding why HIV/AIDS testing was sought. The combined results of this study suggested that the churches surveyed were not promoting HIV/AIDS awareness and that the participants felt that the church should do more as it relates to HIV/AIDS. Conclusions: Since the AA church plays an important role in the lives of many AAs, it potentially can, particularly in rural areas, bring forth social change by advocating HIV/AIDS testing and prevention efforts in order to reduce the rate of HIV infections.